Effect of Partially-Protected Sodium Butyrate and Virginiamycin on Nutrient Digestibility, Metabolizable Energy, Serum Metabolites and Performance of Broiler Chickens - Riboty , R.; Chamba, F.; Puyalto, M.; Mallo, J.J. (International Journal of Poultry Science, 2016)
Continuous use of antibiotics has generated the need of looking for new alternatives in order to decrease emergence of resistant bacteria. The aim of this study was to evaluate the effect of partially-protected sodium butyrate (PPSB) and virginiamycin (VM) on nutrient digestibility, metabolizable energy, serum metabolites and performance of broiler chickens. A complete randomized block design was used with 1071 one- day old Cobb 500® chickens. Three treatments were established: without antibiotics (T1), with 20 ppm of VM (T2) and with 700 ppm of PPSB (T3). Three mash diets were made: starter (1-14 days), grower (15-28 days) and finisher (29-42 days). In experiment 1, performance and serum metabolites were assessed in 903 chicks distributed in 3 treatments of 7 replicates. One chick per replicate was bled at 11 and 31 days. In experiment 2, nutrient digestibility and metabolizable energy were determined in 168 chicks allocated in 3 treatments of 8 replicates. All excreta were collected between 10-13 and 30-33 days. Dry matter, crude protein, fat digestibility, true metabolizable energy and true metabolizable energy corrected by nitrogen were higher with PPSB (p<0.01). Compared with control, VM improved dry matter and crude protein digestibility at 11 days as well as fiber at 31 days (p<0.01) but decreased glucose, cholesterol (p<0.01) and triglycerides (p = 0.04) at 31 days. PPSB also increased cholesterol at 11 days (p = 0.04) and lowered uric acid at 31 days (p = 0.02) respect to control and VM, respectively. Body weight gain and feed conversion ratio were significantly better with PPSB than other treatments. These results suggest that PPSB can be used as a growth promoter in broiler chicken diets.